Computation of stress intensity factor for multiple cracks using singular finite element - Ruslizam, Daud; Ahmad Kamal, Ariffin; Shahrum, Abdullah; A. Emran, Ismail; A., Zulkifli (International Association of Computer Science and Information Technology (IACSIT), 2011)
International Conference on Key Engineering Materials 2011 (ICKEM 2011) organized by International Association of Computer Science and Information Technology (IACSIT), 25th - 27th March 2011 was held at Sanya, China.